Pengaruh Rekam Medis Elektronik Terhadap Efektivitas Pelayanan Di Puskesmas Botania Batam - Situmorang, Masriani; Mulyana, Mulyana; Salsabila, Salsabila (Jurnal Kesehatan Komunitas, 2025)
The development of digital technology has driven the transformation of health services, one of which is through the implementation of Electronic Medical Records (EMR). This study aims to determine the effect of EMR use on the effectiveness of services at the Botania Batam Health Center. The study employed a quantitative descriptive method with a cross-sectional approach. The sample in this study was 32 healthcare workers who used EMR. Data were collected through questionnaires and analyzed using the chi-square test. The results showed that the use of EMR significantly increased the effectiveness of services, especially in terms of the speed of patient data searches, time efficiency, and the quality of medical documentation. However, there are still obstacles such as system disruptions and a lack of training for officers. This study concludes that the implementation of EMR has a positive effect on the effectiveness of services, and it is recommended that routine training and improvements to digital infrastructure continue to be carried out to support system optimization.